Предмет: Алгебра,
автор: imaevartur2015
!!!!!!!!!!!!
НОМЕР 4 ХЕЛП
Приложения:
Ответы
Автор ответа:
0
3(2х+а)^2=12х^2+60x+3a^2
3(4x^2+4ax+a^2)=12x^2+60x+3a^2
12x^2+12ax+3a^2-12x^2-60x-3a^2=0
12ax-60x=0
если x=-4, то
12а*(-4)-60*(-4)=0
-48а+240=0
-48а=-240
а=5
если а=5,то
3(2*(-4)+5)^2=
3(-8+5)^2=
3(64-80+25)=
3*9=27
3(4x^2+4ax+a^2)=12x^2+60x+3a^2
12x^2+12ax+3a^2-12x^2-60x-3a^2=0
12ax-60x=0
если x=-4, то
12а*(-4)-60*(-4)=0
-48а+240=0
-48а=-240
а=5
если а=5,то
3(2*(-4)+5)^2=
3(-8+5)^2=
3(64-80+25)=
3*9=27
Похожие вопросы
Предмет: Литература,
автор: pmalaoaiialo90796
Предмет: ОБЖ,
автор: kalashnikkup
Предмет: Қазақ тiлi,
автор: dkitty41
Предмет: Математика,
автор: panins76